PENGEMBANGAN UNIT PENSUPLAI DAYA BERTENAGA SURYA UNTUK POMPA AIR KELOMPOK TERNAK SAPI DI DAERAH PEDESAAN - Asnawi, Rustam; Yuniarti, Nurhening; Winarto, Felixtianus Eko Wismo (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
In farming, clean water is a basic need to wash food, drink, bathe and clean the cow shed. Provision of clean water is by means of an electric water pump. Meanwhile, electricity prices tend to rise gradually, consequently monthly the electricity bill for farming needs rise. Another thing, the power outage in the countryside sometimes happens in a long duration. The stability of clean water availability at the location of livestock groups is disrupted. One of the best solution approaches to overcome these problems is to create and develop applied products related to renewable energy and energy independence, namely solar power supply unit. This power supply unit uses 2 150WP 12 Volt solar panels, 2 solar charge controllers, 3100Ah batteries and a DC to AC 1500W inverter. The result of the development of this solar powered power supply unit is about 300 Watt. Its main function is to turn on the water pump during the day and in addition it is able to turn on the led light for street lighting at night. Based on the observations, this unit has been operating well and effectively for about 1 month and successfully assisted members of the cow farm groups in the provision of clean water